Essential oil composition and variability of Artemisia herba-alba Asso. growing in Tunisia: comparison and chemometric investigation of different plant organs - Sana Bellilia & b, Wissal Dhific, Abdulrahman Ben Khsif Al-Garnid, Guido Flaminie, Wissem Mnifa & d (Journal of Applied Pharmaceutical Science, 2016)
This study was conceived to investigate the composition of four essential oils (EOs) extracted by hydrodistillation from four parts (leaves, stems, leaves/stems, roots) of Artemisia herba-alba growing wild in the Center of Tunisia. For this, Artemisia herba-alba aerial and roots parts were shade dried with ventilation at room temperature. Then, plant different parts were cut into small pieces and subjected to hydrodistillation using a Clevenger-type apparatus. The gas chromatography (GC) analyses were accomplished with a HP-5890 Series II instrument. The main results showed a total of 152 compounds detected and identified by GC and GC-MS and accounting for 91.3-99.7% of the whole oil. The four oils were characterized by the predominance of monoterpene derivatives (68.2-99.5%) and the major volatile constituent was α-thujone (18.2-45.5%). Qualitative and quantitative differences between the four essential oils have been noted for some compounds. The main compounds of leaves essential oil were α-Thujone (45.5%), β-Thujone (11.4%), trans-sabinyl acetate (10.1%), 1,8-Cineole (7.4%) and camphor (6.8%). α-Thujone (27.5%) was also the main compound in the essential oil of leaves/stems, followed by camphor (22.9%), 1,8-cineole (8.3%), β-thujone (8.2%) and camphene (5.6%). The essential oil of stems was dominated by α-Thujone (28%) followed by β-Thujone (11.4%) and chrysantenone (11%). In the essential oil of roots, α-thujone was less represented (18.2%), followed by camphor (14.6%) and curcumen-15-al (14.3%). It is important to mention that curcumen-15-al has been reported for the first time in Artemisia herba-alba oil Our results revealed avariability in the chemical composition and the yield of the EOs from Artemisia herba-alba. Moreover, curcumen-15-al is a new chemotype first found in Artemisia herba-alba from Tunisia.
Keywords: Artemisia herba-alba,GC-MS, chemical variability, curcumen-15-al.